Procuring Covid-19 Vaccine and the Contemporary Geopolitical Paradigm for Bangladesh - Kazi Md Fahim Ahmed (Business Ethics and Leadership)
Covid-19 has brought unexpected social, political, and economic interruptions to the world, causing endless suffering to people’s lives. As of 19 December 2021, Covid-19 has taken away more than 5 million lives and infected more than 274 million people worldwide. Although many medicines are tested, there is barely any reliable and effective treatment found. The only hope to get out of this pandemic remains concentrated on “Vaccines”. As the nations develop and distribute the Covid-19 vaccines, a potential threat becomes the utilization of vaccine distribution as a soft power tool. So, the major challenge this pandemic has brought is securing vaccine procurement worldwide. Bangladesh, the south Asian developing country, faced a vaccine shortage too. It had to go through various geopolitical struggles and diplomacies to procure vaccines. The fundamental purpose of this study is to review the vaccine procurement opportunities and their relation to the contemporary geopolitical paradigm of Bangladesh. Relevant works of literature consist of journal articles, government statements from multiple countries are reviewed throughout the case. From the beginning to the end of the case, it has been observed that there was a geopolitical power demonstration between India and China regarding the Covid-19 vaccine distribution in Bangladesh. The strong political relation with China, effective diplomacy with the US Biden administration, and a successful diplomatic effort in Japan finally helped Bangladesh to procure a sufficient vaccine for the moment. The research is significant because it connects the pandemic and geopolitics. Although the Covid-19 pandemic is stated as a humanitarian crisis by the great nations, it is clear that it has become an opportunity for many to influence the geopolitical paradigm. If the pandemic has to end, it is vital to distribute vaccines equally throughout the world. The research finds a relation of geopolitical influence with vaccine procurement which destroys equality and reduces the chance of ending the pandemic. This research will bring attention to this important issue in front of the world. In addition, based on this study, other in-depth research could be formed to reduce this global problem.